Pengaruh Karakteristik Dewan Direksi, Karakteristik Komite Audit, dan Manajemen Risiko Terhadap Kinerja Perusahaan - Angelina Putri Faradea; Suwarno Suwarno (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine the effect of the characteristics of the board of directors, the characteristics of the audit committee, and risk management on firm performance. The dependent variable in this study is the firm performance as measured using Tobin's Q. The independent variables in this study are CEO tenure, CEO duality, size of the board of directors, frequency of board of directors meetings, independent board of directors, gender diversity of the board of directors, size of audit committee, frequency of audit committee meetings, independent audit committee, and risk management. The control variables in this study are firm size, leverage, and profitability. The population in this study consists of mining sector companies listed on the IDX. Samples were taken for the years 2017-2021 and collected by purposive sampling method. The total sample of this research is 11 companies. The test was carried out using a partial least square (PLS) approach using WarpPLS 8.0 software. The results of the analysis show that the CEO tenure and the frequency of board of directors meetings have a negative and significant effect on firm performance. The audit committee size and audit committee meeting frequency variables have a positive and significant impact on firm performance. Meanwhile, the CEO duality, the size of the board of directors, the independent board of directors, the gender diversity of the board of directors, the independent audit committee, and risk management have no effect on the firm performance.